Implementation of an expert system for adopting wireless identification technologies (WIT) in healthcare - Barbosa Ávila, J. G.; Diek Assad, Graciano (Revista Mexicana de Ingenieria Biomedica, 2011)
An implementation of an expert system to provide unbiased information about the most suitable technology for specific applications in healthcare. The prototype is developed as a web tool to be used in ordinary personal computers. The idea is to provide with relevant information to health care administration specialists such that they can make appropriate decisions about the selection and implantation of WIT (Wireless Identification Technologies). The expert system prototype can provide expert advise to help critical decision makers in healthcare facilities, health professionals, innovators, and entrepreneurs to select the most suitable technology for the specific application. The system uses membership functions to fire four different figure of merit or indicators: technical feasibility, cost, commercial availability and proven documentation. The advising results are consistent to proven application projects and show high performance dominance using UHF Active RFID for high demanding applications such as new born monitoring and patient assistance. Other non-critical applications such as cabinet monitoring and garement owner ID can be developed using HF or UHF Passive RFID technologies at various frequencies. This prototype follows an effort to create a fundamental platform that could facilitate and stimulate the adoption of WIT in the healthcare industry.